Childhood Victimization, Cognitive Schemas, and Unwanted Consensual Sex Among College Students. Issue 2 (3rd April 2019) - Goodman, Lynnel C.; Hamilton, Lindsay; Koerten, Hannah R.; Mattei, Gina M.; Froemming, Maren W.; Dubow, Eric F.
Abstract: Objective : Unwanted consensual sex (UCS)—freely consenting to sex that is neither wanted nor desired—is largely excluded from campus programming and the literature on sexual behavior. The present study expands on previous research to examine the relation between childhood victimization experiences and UCS. Methods : Data were gathered using an online survey of college students. Results : In the past year, 43% percent of 587 college students who engaged in sexual activity also engaged in UCS at least once. Childhood victimization was modestly related to frequency of UCS. The relation between childhood victimization and UCS was mediated by disconnection/rejection schemas (e.g., beliefs that one's needs will not be met by others). Conclusions : Results suggest that altering cognitive schemas through evidence-based psychotherapy may interrupt the relation between childhood victimization and engagement in UCS.